Petrology, geochemistry and origin of Gapdan Granites (South east of Zahadan) - Habib Biabangard; Shararh Noori (پترولوژی, 2018)
The Gapdan granitoid is located in the southwestern margin of Zahedan granitoid and in the Sistan suture zone. The granitoid under study is composed of granite, monzogranite, granodiorite, pegmatite and diorite. These rocks consist mainly quartz, plagioclase, orthoclase, biotite and hornblende with granular and pegmatite textures. This pluton has intersected by andesitic to dacitic dykes with similar mineralogy with those of the Gapdan granitoid, but they have microlitic and microlitic porphyry textures indicating their formation at a shallow depth and sub-volcanic conditions. The Gapdan granitoid is characterized by metapelitic enclaves with dark-colored and irregular edges with their host pluton and are often enriched in quartz and mica minerals and usually granular texture. Geochemical studies show that the study rocks have calcalkaline to low alkaline magmatic series and metaluminous, I type, LREE and LILE enrichment and depleted in HREE and HFSE. These geochemical characteristics share with those of continental arcs. The amount of Nb / Ce (ave. 0.27) and Nb / La (ave. 0.58) ratios indicate the effect of crustal on the evolution of the Gapdan granite. Tectono magmatic diagrams show the Gapdan granitoid rocks related to syncollision to low post collision environments. According to geochemical data, the study granitoid rocks possibly originated by the rising residual melts from partial melting of oceanic crust (Neo-Tethys) during the collision between the Lut and the Sistan blocks (particularly the Sistan oceanic crust and the mantle wedge overlying it). The continental crust (Flysch and greywake metamorphosed deposit) has been affected the contamination of magma and its formation in post collisional tectonic regimes. Therefore, the Gapdan granitoid may be considered as a hybrid granite type.